Analysis of the Effect of Accounting Information Systems on the Accuracy and Reliability of Financial Statements at Shipping Industry Companies in Surabaya - Gracesheila Florencia Tumbelaka; Nurafni Eltivia; Nur Indah Riwajanti (Komunitas Dosen Indonesia, 2024)
In the contemporary economic landscape, the indispensability of computerized systems, particularly Accounting Information Systems (AIS), is paramount for effective economic activities. This research addresses the knowledge gap surrounding the impact of AIS on the accuracy and reliability of financial statements in the shipping industry companies in Surabaya, Indonesia. The study employs a causal research design with an associative and quantitative approach, involving 57 participants related to AIS in the shipping industry. Utilizing the Integrative Framework of AIS by Romney and Steinbart (2015) and the Financial Reporting Credibility Theory by Dechow and Dichev (2002), the research aims to provide a comprehensive understanding of the relationship between AIS, accuracy, and reliability of financial statements. The findings reveal a positive correlation between AIS implementation and the quality of financial statements, emphasizing the need for effective AIS integration to enhance financial reporting in Surabaya's shipping industry. These results contribute valuable insights for practitioners, researchers, and management in optimizing AIS to support business sustainability and stakeholder confidence amidst dynamic market changes.